ASSOCIATION COVID-19 AND LIVER INJURY : A SYSTEMATIC REVIEW - Giovani, Calista; Monica Carissa, Theodora; Priska Adelin, Claudia (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Most COVID-19 patients present with typical respiratory symptoms (i.e., cough, dyspnea) and fever. However, abnormal liver function is often developed in patients with COVID-19, and liver injury has been related with severe disease. Liver damage ranges from mild asymptomatic elevation of liver enzymes to severe liver injury, while a few cases of acute liver failure have also been reported. The aim: This study aims to show association COVID-19 and liver injury.  Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 44 articles, whereas the results of our search on SagePub brought up 334 articles. The results of the search conducted for the last year of 2013 yielded a total 7 articles for PubMed and 111 articles for SagePub. The result from title screening, a total 4 articles for PubMed and 46 articles for SagePub. In the end, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: COVID-19-associated liver injury is caused by the cumulative effects of multiple factors, including hepatotropic SARS-CoV-2, drug-induced liver injury, hypoxic reperfusion, immune stress and inflammatory factor storms.